One-step synthesis of highly fluorescent carbon dots as fluorescence sensors for the parallel detection of cadmium and mercury ions - Tan, Qiren; Li, Xiaoying; Wang, Lumei; Zhao, Jie; Yang, Qinyan; Sun, Peng; Deng, Yun; Shen, Guoqing (Frontiers in Chemistry, 2022)
Cadmium (Cd2+) and mercury ions (Hg2+) are essential for the quality control of food samples because of their serious toxicity to human health, but the effective and simple strategy for their parallel detection remains challenging. In this paper, a rapid and simple parallel detection method for Cd2+ and Hg2+ was developed using carbon dots (CDs) as fluorescent sensors. A one-step hydrothermal method with a single precursor L-arginine as both the carbon and nitrogen sources was employed to prepare nitrogen-doped CDs (N-CDs). N-CDs exhibited a uniform particle size and excitation-independent fluorescence emission. The maximum emission wavelength of N-CDs was observed at 354 nm with the excitation wavelength at 295 nm. The quantum yield of N-CDs reached as high as 71.6% in water. By using sodium diphosphate and phytic acid as masking agents, the fluorescent sensor can be quenched by Cd2+ and Hg2+ in the linear range of 0–26.8 μM and 0–49.9 μM within 5 min. Other common ions in farm products showed no significant effect on the fluorescence intensity of the sensing system. The results demonstrated that the sensing system had good selectivity and sensitivity for Cd2+ and Hg2+. The detection limits for Cd2+ and Hg2+ were 0.20 μM and 0.188 μM, respectively. In addition, the fluorescent sensor had been successfully applied for the detection of Cd2+ and Hg2+ in fruits and vegetables, and the recoveries were 86.44–109.40% and 86.62–115.32%, respectively. The proposed fluorescent sensor provides a rapid, simple, and sensitive detection method for Cd2+ and Hg2+ in food samples and thus a novel quantitative detection method for heavy metal ions in foods.